Economic costs of hospitalisation and length of stay in diabetes with coexisting hypertension with correlation to laboratory investigations: Where does India stand? A 5‐year ground report. Issue 5 (2nd February 2021) - Sharma, Amit; Baldi, Ashish; Kumar Sharma, Dinesh
Abstract: Introduction: The coexistence of diabetes mellitus (DM) and hypertension (HTN) worsens clinical outcomes and contributes to increased morbidity and mortality. Objective: This study aims to analyse the length of stay and healthcare costs by calculating the direct and indirect costs of diabetes with coexisting hypertension in North India. Methods: A prospective observational study was conducted at the medicine department of the three different hospitals. Results: The patients' mean age was (M = 53.8, SD = 11.5) years. Out of 1914 patients, 53.65% were female. Our study revealed that the median cost of medical supplies and equipment was 21.2 . The median cost of dialysis was 47.5 ; the median cost of hospitalisation was 142.6 . The treatment's median direct cost was 188.5 , followed by the overall median cost of 295.6 . The maximum overall cost of treatment was observed at 603.9 . It was observed that maximum LOS was 14 days for patients having BPS between 140 and 159 mmHg and BPD between 110 and 119 mmHg, and minimum LOS was found 3.5 days. Conclusion: The present study highlighted that diabetes coexisting hypertension poses a high‐economic burden on patients. This study explored that highly significant result for BPS, BPD, FBS and HbA1 c, whereas the significant results were obtained when RBS is compared with LOS and treatment costs. Our study concluded that mean difference of 9.24 in patients having FBS was 261‐290 mg/dL and >290 mg/dL. The LOS is increased by 6.57 days for patients with BPS between 140 and 159 mmHg compared with BPS between 180 and 209 and above mmHg, which lowers treatment costs by −21.31.